The tale of Pigling Bland - Potter, Beatrix, 1866-1943 (Potter, Beatrix, 1866-1943. Peter Rabbit books., 1913)
Pigling sets off from home and, among his adventures, helps Pig-wig escape from Mr. Piperson.